Pengaruh Promosi, Digital Marketing dan E-wom terhadap Keputusan Pembelian Online dengan Kepuasan Konsumen sebagai Variabel Mediasi - Leonardo Davidsi Sipayung (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to analyze the effect of promotion, digital marketing, and e-wom as independent variables on online purchasing decisions as the dependent variable through consumer satisfaction as a mediating variable. The test analysis model uses the outer model, inner model, direct effects, and specific indirect effects using the Smart PLS 4 application. Directly, the results of this study indicate that promotions, e-WOM, and consumer satisfaction have a positive and significant effect on online purchasing decisions, while digital marketing has no significant effect on online purchasing decisions. Digital marketing and e-wom have a positive and significant effect on consumer satisfaction, while promotions have no significant effect on customer satisfaction. Indirectly, digital marketing and e-wom have a positive and significant effect on online purchasing decisions through consumer satisfaction. Meanwhile, promotions have no significant effect on online purchasing decisions through consumer satisfaction.